A remarkable pattern of a tibial plateau fracture - use of a safe technique with practical advantages in the surgical field - Touloupakis, Georgios; Ghirardelli, Stefano; Biancardi, Elena; Bibiano, Luigi; Antonini, Guido; Crippa, Cornelio (Acta Biomedica Atenei Parmensis, 2019)
Bicondylar plateau fractures are complex injuries often requiring a challenging treatment. We report a case of a 68 year-old-male patient with a complicated tibial plateau bicondylar fracture. The fracture of the tibial plateau involved all columns (lateral, medial, posterior). The fracture pattern of the proximal tibia managed by triple plating through dual posteromedial and anterolateral incisions. Posterior-medial and the medial plating result in increased stability. The posteromedial approach to the knee that we used in our case, offers various advantages. We recommend the option of the posteromedial access, as an approach that allows excellent control of the posterior involvement of this pattern of tibial plateau fracture.